The Determinants of Productivity Distribution across European Regions - Davide Fiaschi; Andrea Mario Lavezzi; Angela Parenti (European Regional Science Association (ERSA), 2010)
This paper proposes a methodology which combines elements of parametric regression analysis with the nonparametric distribution dynamics approach in order to analyse the role of some variables in the convergence of productivity across European regions over the period 1980-2002. We find that the initial productivity crucially accounts in the convergence process across European regions. Differently, employment growth seems not to play a role, while the Structural and Cohesion Funds seem to play a positive role, even though such effect seems to be very low and statistically significant only at the low bound of the range of initial productivity. The structural change of regional economies plays a positive role, but such effect is statistically significant only for the least productive regions. The output composition of a region in 1980 affects the convergence process of productivity growth in several ways. In particular, the share of non market services on output acts like a source of convergence from 1980 to 2002 but in the long-run it plays a negligible role. Finally, the share of finance acts like a force of divergence across European regions, especially for the least productive regions.
Keywords: C21; E62; R11; O52; 330; European regional policy; structural change; convergence; European regions; outputcomposition; distribution dynamics; polarization